2008
DOI: 10.1080/15287390801987998
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Genetic Polymorphisms in Styrene-Metabolizing Enzymes and Biomarkers in Styrene-Exposed Workers∗

Abstract: Single-nucleotide polymorphisms (SNP) in genes of styrene-metabolizing enzymes could modulate biomarker concentrations in blood or urine after exposure to styrene. Ten SNP were analyzed to study their influence on styrene-specific biomarkers in 89 workers of a fiber-reinforced plastic boat building factory. The internal styrene body burden was analyzed in post-shift blood and urine samples. External styrene exposure was measured by passive samplers. Spearman rank correlations between styrene exposure and bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They show the role of enzymes of xenobiotic metabolism in the formation of the individual sensitivity of workers in the context of hazardous industries. 19,20 In the study by Ma, et al, it was found that the Ile/Val and Val/Val genotypes are associated with a predisposition to bladder cancer caused by benzidine. 21 The results from this study indicate a selection of the homozygous Val/ Val genotype in the group of healthy workers perhaps in favor of its protectivity, confirmed by Mapp, et al, indicating the protective value of the Val/Val genotype in workers exposed to isocyanate.…”
Section: Discussionmentioning
confidence: 99%
“…They show the role of enzymes of xenobiotic metabolism in the formation of the individual sensitivity of workers in the context of hazardous industries. 19,20 In the study by Ma, et al, it was found that the Ile/Val and Val/Val genotypes are associated with a predisposition to bladder cancer caused by benzidine. 21 The results from this study indicate a selection of the homozygous Val/ Val genotype in the group of healthy workers perhaps in favor of its protectivity, confirmed by Mapp, et al, indicating the protective value of the Val/Val genotype in workers exposed to isocyanate.…”
Section: Discussionmentioning
confidence: 99%